Fibroblast growth factor‐2 promotes healing of surgically created periodontal defects in rats with early, streptozotocin‐induced diabetes via increasing cell proliferation and regulating angiogenesis. (5th December 2014) - Bizenjima, Takahiro; Seshima, Fumi; Ishizuka, Yoichi; Takeuchi, Takahiro; Kinumatsu, Takashi; Saito, Atsushi
Abstract Aim To evaluate the effects of fibroblast growth factor (FGF)‐2 on the healing of surgical periodontal defects in rats with early, streptozotocin‐induced diabetes. Materials and Methods Fifty Wistar rats were assigned to streptozotocin‐induced diabetes or non‐diabetes group. Periodontal defects were surgically created at maxillary first molars. Defects were treated with hydroxypropyl cellulose (HPC) or FGF‐2 with HPC. Defect fill was evaluated by microcomputed tomography. Histological and immunohistochemical analyses were performed. Results Compared to vehicle alone, FGF‐2 treatment yielded significantly greater bone volume and trabecular thickness in diabetes group. Diabetes group displayed reduced new bone formation and significantly longer epithelial down‐growth compared to non‐diabetes group. In diabetes group, FGF‐2 treatment increased PCNA‐positive cells and new bone formation after 2 weeks and suppressed epithelial down‐growth, but new cementum formation was minimal even after 4 weeks. In diabetes group, overexpression of vascular endothelial growth factor was evident in cells within connective tissue, and no significant enhancement was observed by FGF‐2 treatment. FGF‐2 increased the expression of α‐smooth muscle actin in diabetes group. Conclusions Treatment of surgical periodontal defects in diabetic rats with the single application of FGF‐2 provided beneficial effects primarily on new bone formation via increasing cell proliferation and regulating angiogenesis.